Musical rhythm discrimination explains individual differences in grammar skills in children. Issue 4 (7th September 2014) - Gordon, Reyna L.; Shivers, Carolyn M.; Wieland, Elizabeth A.; Kotz, Sonja A.; Yoder, Paul J.; Devin McAuley, J.
Abstract This study considered a relation between rhythm perception skills and individual differences in phonological awareness and grammar abilities, which are two language skills crucial for academic achievement. Twenty‐five typically developing 6‐year‐old children were given standardized assessments of rhythm perception, phonological awareness, morpho‐syntactic competence, and non‐verbal cognitive ability. Rhythm perception accounted for 48% of the variance in morpho‐syntactic competence after controlling for non‐verbal IQ, socioeconomic status, and prior musical activities. Children with higher phonological awareness scores were better able to discriminate complex rhythms than children with lower scores, but not after controlling for IQ. This study is the first to show a relation between rhythm perception skills and morpho‐syntactic production in children with typical language development. These findings extend the literature showing substantial overlap of neurocognitive resources for processing music and language. A video abstract of this article can be viewed at: http://youtu.be/_lO692qHDNg